Beispiel Nr: 23
$ \text{Gegeben:} \\ \text{Lineares Gleichungssytem} \\ a1 \cdot x_1 + b1\cdot x_2 + c1\cdot x_3 ....=d1 \\ a2\cdot x_1 + b2\cdot x_2 + c2\cdot x_3 .....=d2\\ a3\cdot x_1 + b3\cdot x_2 + c3\cdot x_3....=d3\\ ..... \\ \text{Gesucht: }x_1,x_2,x_3.... \\ \\ $
$\textbf{Aufgabe:}$ w
$\textbf{Rechnung:}\\ \small \begin{array}{l} 2x_1+3x_2+x_3=15 \\ x_1+3x_2+x_3=11 \\ 3x_1+2x_2+2x_3=18 \\ \\ \end{array} \qquad \small \begin{array}{ccc|cc } x_1 & x_2 & x_3 & & \\ \hline2 & 3 & 1 & 15 \\ 1 & 3 & 1 & 11 \\ 3 & 2 & 2 & 18 \\ \end{array} \\ \\ \small \begin{array}{l}\text{Zeile}2=\text{Zeile}2\text{-Zeile}1\cdot \frac{1}{2}\\z2s1=1-2\cdot \frac{1}{2}=0 \\ z2s2=3-3\cdot \frac{1}{2}=1\frac{1}{2} \\ z2s3=1-1\cdot \frac{1}{2}=\frac{1}{2} \\ z2s4=11-15\cdot \frac{1}{2}=3\frac{1}{2} \\ \end{array}\qquad \small \begin{array}{ccc|cc } x_1 & x_2 & x_3 & & \\ \hline2 & 3 & 1 & 15 \\ 0 & 1\frac{1}{2} & \frac{1}{2} & 3\frac{1}{2} \\ 3 & 2 & 2 & 18 \\ \end{array} \\ \\ \small \begin{array}{l}\text{Zeile}3=\text{Zeile}3\text{-Zeile}1\cdot \frac{3}{2}\\z3s1=3-2\cdot \frac{3}{2}=0 \\ z3s2=2-3\cdot \frac{3}{2}=-2\frac{1}{2} \\ z3s3=2-1\cdot \frac{3}{2}=\frac{1}{2} \\ z3s4=18-15\cdot \frac{3}{2}=-4\frac{1}{2} \\ \end{array}\qquad \small \begin{array}{ccc|cc } x_1 & x_2 & x_3 & & \\ \hline2 & 3 & 1 & 15 \\ 0 & 1\frac{1}{2} & \frac{1}{2} & 3\frac{1}{2} \\ 0 & -2\frac{1}{2} & \frac{1}{2} & -4\frac{1}{2} \\ \end{array} \\ \\ \small \begin{array}{l}\text{Zeile}1=\text{Zeile}1\text{-Zeile}2\cdot \frac{3}{1\frac{1}{2}}\\z1s2=3-1\frac{1}{2}\cdot \frac{3}{1\frac{1}{2}}=0 \\ z1s3=1-\frac{1}{2}\cdot \frac{3}{1\frac{1}{2}}=0 \\ z1s4=15-3\frac{1}{2}\cdot \frac{3}{1\frac{1}{2}}=8 \\ \end{array}\qquad \small \begin{array}{ccc|cc } x_1 & x_2 & x_3 & & \\ \hline2 & 0 & 0 & 8 \\ 0 & 1\frac{1}{2} & \frac{1}{2} & 3\frac{1}{2} \\ 0 & -2\frac{1}{2} & \frac{1}{2} & -4\frac{1}{2} \\ \end{array} \\ \\ \small \begin{array}{l}\text{Zeile}3=\text{Zeile}3\text{-Zeile}2\cdot \frac{-2\frac{1}{2}}{1\frac{1}{2}}\\z3s2=-2\frac{1}{2}-1\frac{1}{2}\cdot \frac{-2\frac{1}{2}}{1\frac{1}{2}}=0 \\ z3s3=\frac{1}{2}-\frac{1}{2}\cdot \frac{-2\frac{1}{2}}{1\frac{1}{2}}=1\frac{1}{3} \\ z3s4=-4\frac{1}{2}-3\frac{1}{2}\cdot \frac{-2\frac{1}{2}}{1\frac{1}{2}}=1\frac{1}{3} \\ \end{array}\qquad \small \begin{array}{ccc|cc } x_1 & x_2 & x_3 & & \\ \hline2 & 0 & 0 & 8 \\ 0 & 1\frac{1}{2} & \frac{1}{2} & 3\frac{1}{2} \\ 0 & 0 & 1\frac{1}{3} & 1\frac{1}{3} \\ \end{array} \\ \\ \small \begin{array}{l}\text{Zeile}2=\text{Zeile}2\text{-Zeile}3\cdot \frac{\frac{1}{2}}{1\frac{1}{3}}\\z2s3=\frac{1}{2}-1\frac{1}{3}\cdot \frac{\frac{1}{2}}{1\frac{1}{3}}=0 \\ z2s4=3\frac{1}{2}-1\frac{1}{3}\cdot \frac{\frac{1}{2}}{1\frac{1}{3}}=3 \\ \end{array}\qquad \small \begin{array}{ccc|cc } x_1 & x_2 & x_3 & & \\ \hline2 & 0 & 0 & 8 \\ 0 & 1\frac{1}{2} & 0 & 3 \\ 0 & 0 & 1\frac{1}{3} & 1\frac{1}{3} \\ \end{array} \\ \\ x_1=\frac{8}{2}=4\\x_2=\frac{3}{1\frac{1}{2}}=2\\x_3=\frac{1\frac{1}{3}}{1\frac{1}{3}}=1\\L=\{4/2/1\}$